EL PROYECTO "LEVENE" (H) DE CÃ“DIGO PROCESAL PENAL PARA LA JUSTICIA NACIONAL ARGENTINA - Rivas, Adolfo Armando (Revistas ICDP, 2015)
EL PROYECTO "LEVENE" (H) DE CÃ“DIGO PROCESAL PENAL PARA LA JUSTICIA NACIONAL ARGENTINA